SEXUAL VIOLENCE IN UNIVERSITIES: PREVENTION MEASURES AND HANDLING OF THE CONCEPT OF PERMENDIKBUD NO 30 OF 2021 AND ISLAMIC PERSPECTIVE - Atikah Rahmi (Proceeding International Seminar of Islamic Studies, 2022)
Crime with the mode of sexual violence is a crucial problem has faced today, because it occurs in all lines of society, including in universities. Campus should be a place to give birth to a generation of intellectuals as agents of change to create peace, but due to unequal power relations, sexual violence occurs. This paper is a normative research, using Permendikbud No. 30 of 2021 as an analytical knife for handling sexual violence in universities and a study of some literature and online media. In addition, the Maqashid sharia approach is used to explain that sexual violence is contrary to the goal of Islam to realize the benefit. Sexual violence shows the loss of the perpetrator's morals which is the core of his humanity and has an impact on the loss of the benefit of the victim in various aspects of life. Effective handling is very urgent to provide justice for victims and as an effort to prevent recurrence. Permendikbud 30 of 2021 is the legal umbrella for acts of sexual violence that occur in universities, by establishing a task force for prevention and handling of victims.Keywords: Sexual Violence, Prevention.